A Cyber Da’wah Communication Model: Strategies and Message Effectiveness on Social Media - Beni Pramula (Journal of Noesantara Islamic Studies, 2025)
The rapid development of digital communication technology has significantly transformed the practice of da’wah, particularly through the use of social media as a primary platform for conveying Islamic messages. This study analyzes a cyber da’wah communication model by focusing on communication strategies, interaction patterns, and message effectiveness across social media platforms such as Instagram, YouTube, TikTok, and X. Employing a qualitative approach based on literature review and observation of digital da’wah content, this research finds that effective cyber da’wah depends not only on message substance but also on the da’i’s ability to adapt communication styles to platform characteristics. Strategies such as storytelling, the use of simple and relatable language, visual and audiovisual integration, and consistent content production are essential. Moreover, cyber da’wah promotes participatory and interactive communication, enabling audiences to actively engage in discussions and feedback. Message effectiveness is influenced by communicator credibility, message clarity, relevance to contemporary issues, and digital literacy.